(untitled) (Indian Journal of Arid Horticulture, 2025)
An experiment on the "Screening of Amaranthus genotypes for yield and quality under semiarid condition of western India" was conducted using twenty eight accessions including released varieties were collected from diversified areas. The experiment was laid out in a randomized complete block design with three replications. The experiment results revealed that the significant differences among the genotypes for all the characters under study indicating the wide variability present in the germplasm. Among the genotypes studied in the present experiment, the highest plant height was recorded in IC-4469674 followed by IC-469676. The leaf size is considered an important character which decided by the leangth and breadth of the leaf. Arka Suguna, IC-469646, IC-469620, IC-469601 and IC-464521 recorded the lengthiest leaves over 10.0cm against IC-469645 (5.0cm). Arka Suguna, IC-469646, IC-469620 recorded the higher leaf breadth over 7.0cm against IC-469624 (2.6cm). The highest total leaf yield per plot was recorded in Arka Suguna (5.66 Kg) followed by Arka Arunima and IC-469646. This result indicate that the Arka Suguna, IC-469646, IC-469620 are broader leafy type and would be preferred by consumers. Study on quality parameters indicated that the highest protein (3.8g) and Fe (0.521mg) per 100 g has been recorded in IC-469646. Hence, Arka Suguna (Green type) and Arka Arunima (purple type) have exhibited a high yielding genotypes and IC-469646 (Green type) has registered high yield coupled with high protein and high Fe content under semiarid condition.